Spatial Filtering Velocimetry Fundamentals and Applications - Aizu, Yoshihisa; Asakura, Toshimitsu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
The first monograph devoted exclusively to spatial filtering velocimetry, this book includes fundamental theory, imaging optics, signal analysis, spatial filtering devices and systems, plus applications. Also suitable as a tutorial for students and users who are unfamiliar with optics and signal processing, Spatial Filtering Velocimetry treats the principle and properties of this velocimetric technique in a concise and easily readable form, together with full appendices. The book reviews a wide range of systems and applications of the spatial-filtering technique for velocity and related measurements, putting forth examples useful in various fields of science, medicine, and engineering.
Introduction -- Principle and Properties of the Spatial Filtering Method -- Optical System -- Signal Analysis -- Spatial Filtering Devices and Systems -- Applications -- Fourier Analysis -- Power Spectral Density of the Signal -- Derivation of (2.12) -- Derivation of (2.20) and (2.21) -- Power Spectra for Spatial Filters in Sect. 2.3 -- Derivation of (2.45) -- One-Dimensional Power Spectrum of the Signal -- Derivation of Output Signals for Visibility Analysis.
Keywords: Physics; Optics; Optoelectronics; Plasmons (Physics).; Engineering; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Electronic books